Promoting health awareness through participatory education to prevent stunting and infectious diseases - Wiwin Dwi Astuti; Vaneza Kalemma Sadiyah; Rekhan Jarwanto (Universitas Pendidikan Indonesia, 2025)
Public health is a crucial foundation for achieving an optimal quality of life, particularly through participatory efforts aimed at preventing stunting and controlling infectious diseases at the community level. This community service aims to improve community understanding and practice of stunting and infectious disease prevention through a participatory and collaborative approach. The activity was conducted in Mertoyudan District, Magelang Regency, with 30 housewives serving as the primary participants. The implementation method consists of three stages: planning, implementation, and follow-up evaluation. Education focuses on clean and healthy living patterns (Perilaku Hidup Bersih dan Sehat or PHBS), sanitation management, and disease prevention. The evaluation results showed a significant increase in participant understanding, as indicated by a rise in the average scores on the pretest and posttest for the topics of stunting and infectious diseases. However, a gap remains between knowledge and the implementation of healthy behaviors due to limited access to healthcare facilities. Therefore, the recommended follow-up is a motivation-based approach and strengthening the role of women as agents of change. This program contributes to supporting sustainable national health development. Abstrak Kesehatan masyarakat merupakan fondasi penting dalam mewujudkan kualitas hidup yang optimal, terutama melalui kegiatan pencegahan stunting dan pengendalian penyakit menular secara partisipatif di tingkat komunitas. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan praktik masyarakat terhadap pencegahan stunting dan penyakit menular melalui pendekatan partisipatif dan kolaboratif. Kegiatan dilaksanakan di Kecamatan Mertoyudan, Kabupaten Magelang dengan melibatkan 30 ibu rumah tangga sebagai peserta utama. Metode pelaksanaan terdiri dari tiga tahap: perencanaan, pelaksanaan, serta evaluasi tindak lanjut. Edukasi difokuskan pada pola hidup bersih dan sehat (PHBS), pengelolaan sanitasi, dan pencegahan penyakit. Hasil evaluasi menunjukkan peningkatan signifikan pemahaman peserta, ditunjukkan oleh kenaikan skor rata-rata pretest dan posttest pada topik stunting dan penyakit infeksi. Meski demikian, masih ditemukan kesenjangan antara pengetahuan dan implementasi perilaku sehat akibat keterbatasan fasilitas kesehatan. Oleh karena itu, tindak lanjut yang direkomendasikan adalah pendekatan berbasis motivasi dan penguatan peran perempuan sebagai agen perubahan. Program ini berkontribusi dalam mendukung pembangunan kesehatan nasional yang berkelanjutan. Kata Kunci: edukasi partisipatif; kesehatan masyarakat; penyakit menular; stunting